(untitled) (Revista de Crítica Literaria Latinoamericana, 2022)
The works of writer Mariano Azuela have been considered a touchstone in order to appreciate the narratives of the Mexican Revolution. Here, I aim to examine Azuela’s work in a different, more ambiguous way; I show how the short story “Andrés Pérez, maderista” employs some of the most salient themes of the Porfiriato—primarily, journalism and science. To focus solely on the insurrec- tionary aspects of Azuela’s text would be to ignore the historical context in which Azuela created his work. Ultimately, to see Azuela’s text as merely “Revolutionary” is to diminish the story’s complexity.